Effect of certain commercial compounds in controlling root-knot nematodes infected potato plants - Mostafa, Fatma A.; Ali, R. A.; Zawam, Hanaa S. (Journal of Phytopathology and Disease Management, 2015)
To examine the effect of certain commercial compounds against root-knot nematode (Meloidogyne incognita) which infect potato plants (Solanum tuberosum L. var. sponta). Two experiments were carried out under laboratory and field conditions during 2012 and 2013 seasons. Eight nematicides were used as treatments i.e., Mocap, Super control, Dento, Nematex, Vertimyl, Oxamyle, Bionematone, and Bioxy+. The successful treatments were chosen due to their effectiveness on percentage reduction in nematode populations, maximize plant production. The chosen treatments applied in soil naturally infected with nematode in the experimental field in Nubaria, Behira Governorate, North Egypt. Results exhibited significantly reduction in all nematode developmental stages in plant and soil, ex. number of egg masses, galls and nematodes in 250 cm3 soil with all chemical compounds. The consequence of vegetative growth parameters and yield were increased significantly with tested treatments compared with control. Moreover, results of laboratory experiments recorded that 87 to 98% inhibition for egg-masses hatching and 85 to 98% mortality for juveniles, respectively, with 90% for the lethal concentration of Bioxy+, Oxamyl and Vertimyl.